Analysis of how the european stock markets perceive the dynamics of macroeconomic indicators through the sentiment index and the purchasing managers' index - Iulia Lupu (Financial Studies, 2018)
In this article, we intend to analyse how the European stock markets perceive the dynamics of macroeconomic indicators in terms of the sentiment index and the purchasing managers' index. For this research, we focused on the countries of the European Union and applied an econometric event study, which consisted in the analysis of the evolution of the logarithmic returns of the stock indices for 27 countries of the European Union and for the euro area for the period January 2007 - November 2017. The results showed immediate reactions with a higher intensity in March 2015 for the SentiMent index and for March 2016 for the PMI. The frequency and amplitude of reactions are different from country to country; often, a high frequency of reactions in one country is not reflected in a very high amplitude response.
Keywords: G19; G32; 330; capital markets; sentiment indices